PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAQUL KARIMAH SISWA - Suprihatin Suprihatin (AT-TAJDID, 2019)
The main function of the teacher is as a role model for his students. That is, that a teacher must be an example and role model, arouse learning motivation and encourage students from behind. The teacher is a human figure who occupies the most important position in education. Teachers as central in the world of education. Exemplary is one of the methods of education that has a big influence on the success of the teaching and learning process. The Islamic system in improving children is based on two basic principles, namely teaching and habituation. The purpose of teaching (Talqin) here is to approach theoretical aspects in efforts to improve children.Keywords. Role, teacher, fostering, morals